VARIATIONS IN THE OSMIUM ISOTOPE COMPOSITION OF SEAWATER OVER THE PAST 200 000 YEARS - Oxburgh R. (My University, 1998)
The first osmium isotope data are presented for marine sediments spanning the past 200,000 years (two full glacial cycles) and establish that there have been ocean-wide variations in sea-water osmium isotope composition over this time. While the osmium isotope composition of sea water has been relatively invariant over much of this interval (187Os/186Os of 8.5 to 8.6), excursions to lower isotope ratios (187Os/186Os ≈ 8.1) occur late in the last two glacial periods at 20 ka and 160 ka. These are times of high global aridity, low global temperature and maximum ice extent. While various interpretations are possible, a likely explanation is that the low sea-water ratios reflect reduced chemical weathering of the continents during times of extreme cold and aridity. There is no evidence that there is a net enhancement of chemical weathering during periods of continental glaciation. The response of ocean composition to changes in input flux constrain the oceanic residence time of osmium to be less than 12,000 years.